Determining health promoting behaviours, self-rated health, life satisfaction and loneliness among older persons - Ozvurmaz, Safiye; Adana, Filiz; Mandiracioglu, Aliye (Journal of the Pakistan Medical Association, 2022)
Objective: To determine relationship between health-promoting behaviours and loneliness, and between life satisfaction and self-rated health among the elderly. Method: The cross-sectional study was conducted from June to November 2020 in Aydin, Turkey, after approval from the ethics review committee at Ege University, Izmir, Turkey, and comprised individuals of either gender aged >65 years. Data was collected through face-to-face interviews using a data-collection form with questions to identify independent variables and the geriatric health protective behaviour scale. Data was analysed using SPSS 23. Results: Of the 661 subjects, 334(50.5%) were females and 327(49.5%) were males. The largest group was of those aged 65-69 years 270(40.8%), while the smallest group comprised those aged 74-79 years 94(14.2%). Overall, 19(2.9%) subjects perceived their health as very good, while 161(24.4%) described it as good. Subjects aged 65-69 years, who had secondary education, whose perception of household income was good, who were not disabled, who did not feel lonely and who were regularly visited had higher scores (p<0.05). Conclusion: Health-promoting behaviours are affected by an individual’s socioeconomic conditions as well as their life satisfaction, feeling of loneliness and perception of health. Key Words: Geriatrics, Geriatric health promotion scale, Health promotion, Health of the elderly.